THE DIAGNOSTIC VALUE OF ADJACENT MUCOZAL DIFFERENCES IN GASTRIC ULCERS - Bülent KARA; Belkıs ÜNSAL; M. Kadir AKSÖZ; Günay ÖNDER; Nafi YAZICIOĞLU; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-